The Impact of Changing Electoral Systems on Women’s Political Representation in Iraq: An Analytical Study in Light of the 2005 Constitution - Ruqayya Maytham Abdul-Hussein Mohammed Redha (International Journal of Law Research and Studies, 2026)
The issue of women's political representation in Iraq is no longer confined to the absence of constitutional provisions, but rather lies in the instability of the governing "electoral system." This study aims to measure the impact of legislative variables (changing electoral laws) on the effectiveness of women's participation, by analyzing the dialectical relationship between "constitutional stability" represented by the Quota (Article 49) and "legislative turbulence" represented by the fluctuation of laws between the Proportional Representation system (Sainte-Laguë) and the Multi-District system. The research adopts a descriptive-analytical approach supported by a statistical reading of election outcomes (2010-2021) and a review of the historical development of political rights. The study concludes that there is a direct correlation between the electoral system type and the quality of female representation; while the "Sainte-Laguë" system entrenched women's subordination to party leaders (the Proxy MP phenomenon), the "Multi-District" system in the 2021 elections caused a qualitative leap, enabling 57 women to win by their own votes, exceeding the constitutional quota ceiling. The research also discusses the structural challenges (political violence, funding, patriarchal dominance) facing women, offering a forward-looking vision to evolve the Quota from a "protection" mechanism into a "competition" base.
Keywords: Electoral Systems; Women’s Quota; 2005 Constitution; Sainte-Laguë; Multi-District; Political Empowerment